Awareness Regarding Cyber Victimization among Students of University of Sindh, Jamshoro - Avais, Muhammad Abdullah; Wassan, Aijaz Ali; Narejo, Hameeda; Khan, Jameel Ahmed (International Journal of Asian Social Science, 2014)
The crimes that are committed by computers and networks called cybercrimes. The aim of study is to know the awareness towards cyber victimization among students of university of Sindh Jamshoro. 100 students (50% male and female) were selected through purposive sampling. The result shows that 77% respondents don’t bother to share their personal informations with cyber friends. Only 41 % respondents like to read policy guidelines of any social networking site. 57 % respondents use internet more than 06 hours on daily basis. 82% respondents believe that women are more prone to cyber attacks. 73% respondents don’t know regarding any government department for their help in case of cyber victimization.